Endogenous Hypercortisolism in recurrent Central Serous Chorioretinopathy - Sushmita Mukherji; Soumen Karmakar; Sibaji Dasgupta (Asian Journal of Medical Sciences, 2021)
Background: Central Serous Chorioretinopathy (CSCR) is an important cause of nonsurgical retinopathy leading to moderate to severe visual loss. Almost 50% cases undergo recurrence, and one of the recognizable risk factors is endogenous hypercortisolism.